Weil’s disease with cutaneous manifestation - Manappallil, Robin George; Krishnan, Ashish Pappinisseri (Indian Journal of Case Reports, 2019)
Leptospirosis can present with a wide range of clinical manifestations. Its severe form, called Weil’s disease, can result in multiorgan dysfunction and death. Hence, an early diagnosis is very essential. The patient being reported had a fever with maculopapular rash, which was initially treated as viral fever. He was later diagnosed to have Weil’s disease; which improved with penicillin therapy. Cutaneous manifestation in leptospirosis is uncommon, and awareness about this can help to prevent life-threatening complications.